The Effect of using (TRIZ) theory in the collection of basic Fourth -grade students in Social Studies An experimental study in Damascus (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research aimed at recognizing the efficiency of using (TRIZ) theory in the collection of basic fourth- grade students in Social Studies, this study was adopted on experimental approach. The research tool formed of achievement test. The research sample consisted of (50) male and female students divided into two groups: an experimental group consisted of (25) male and female students of Safia Al-qurashia school studied by (TRIZ) theory, and a control group consisted of (25) male and female students of the same school studied by traditional manner. The findings of the study were as follows: - There were significant statistical differences between the mean scores of students in the experimental group for the pre and post of achievement test as a whole, and at every level of low knowledge levels in favor of the post application. - There were significant statistical differences between the mean scores of students of the experimental group and the control group in the post to achievement test as a whole, and at every level of low knowledge levels in favor of the experimental group. هدف البحث إلى تعرّف أثر برنامج تعليمي قائم على نظرية (تريز) في تحصيل تلاميذ الصف الرابع الأساسي في مادة الدراسات الاجتماعية في مدينة دمشق، اعتمد البحث المنهج شبه التجريبي، وتكونت أدوات البحث من اختبار تحصيلي، بلغت عينة البحث (50) تلميذاً وتلميذة، قسمت إلى مجموعتين، مجموعة تجريبية تكونت من (25) تلميذاً وتلميذة من مدرسة صفية القرشية تعلّمت وفق نظرية (تريز)، ومجموعة ضابطة تكونت من (25) تلميذاً وتلميذة من نفس المدرسة تعلّمت بالطريقة المعتادة، وأشارت نتائج البحث إلى الآتي: -      توجد فروق ذات دلالة إحصائية بين متوسطات درجات تلاميذ المجموعة التجريبية في التطبيقين القبلي والبعدي المباشر للاختبار التحصيلي في كل مستوى من مستوياته المعرفية الدنيا لصالح التطبيق البعدي. -      توجد فروق ذات دلالة إحصائية بين متوسطات درجات تلاميذ المجموعة التجريبية وتلاميذ المجموعة الضابطة في التطبيق البعدي للاختبار التحصيلي في كل مستوى من مستوياته المعرفية الدنيا لصالح المجموعة التجريبية. -               ويقترح إجراء دراسة مماثلة للدراسة الحالية تتناول مبادئ إبداعية أخرى لنظرية (تريز) تساعد على رفع مستوى التحصيل الدراسي.